Teacher Training for Content and Language Integrated Learning at the University - P. V. Sysoyev (Высшее образование в России)
A relatively new approach to teaching students of non-linguistic areas of education and specialties in a foreign language and profile specialty is Content and Language Integrated Learning (CLIL). The uniqueness of the approach lies in the fact that in the course of one integrated course students simultaneously master both a professional foreign language and a specialized discipline or specialty. However, the implementation of this approach in practice requires the  formation of a number of professional competencies in an integrated course teacher: foreign language communicative competence, competence in a  specialized specialty, competence in the methodology of teaching a foreign language and the specialized specialty. This paper presents the experience of the Derzhavin Tambov State University in developing a personnel reserve program aimed at training teachers of integrated courses.